2020
DOI: 10.1136/bmjsem-2019-000707
|View full text |Cite
|
Sign up to set email alerts
|

Movement pattern training compared with standard strengthening and flexibility among patients with hip-related groin pain: results of a pilot multicentre randomised clinical trial

Abstract: Study designPilot, multicentre randomised clinical trial (RCT).ObjectivesAssess viability of performing a definitive RCT and compare preliminary effects of movement pattern training (MoveTrain) and strengthening/flexibility (Standard) to improve function in people with chronic hip-related groin pain (HRGP).BackgroundTo determine the best physical therapist-led intervention for patients with HRGP, we must understand treatment effects of different treatment modes.MethodsForty-six patients (17M:29F; 29±5.3 years;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…This was a cross-sectional study designed to use baseline data from a pilot multisite randomized clinical trial for patients with HRGP. 16 Only patients enrolled at the Washington University site were included in the current study as additional funding allowed for collection of 3D kinematic data. Data collection occurred at The Movement Science Research Center at Washington University in St. Louis, Missouri.…”
Section: Methods Designmentioning
confidence: 99%
“…This was a cross-sectional study designed to use baseline data from a pilot multisite randomized clinical trial for patients with HRGP. 16 Only patients enrolled at the Washington University site were included in the current study as additional funding allowed for collection of 3D kinematic data. Data collection occurred at The Movement Science Research Center at Washington University in St. Louis, Missouri.…”
Section: Methods Designmentioning
confidence: 99%
“…We completed a pilot, multicenter RCT (ClinicalTrials.gov: NCT02913222) comparing two PT-led interventions for HRGP, movement pattern training (MoveTrain) and traditional strength and flexibility training (Standard) to establish feasibility of completing a definitive trial. 8 We established feasibility and reported that both strategies resulted in clinically significant improvements in patientreported function and hip muscle strength immediately after treatment. 8 The MoveTrain group also demonstrated an improvement in lower extremity movement patterns.…”
Section: Introductionmentioning
confidence: 98%
“…A growing body of evidence suggests that PT-led intervention can decrease pain and improve function among patients with HRGP. [6][7][8][9][10][11][12][13][14] Most studies report short-term outcomes only and do not report if effects are sustained past the active treatment phase. Only two studies report outcomes 1 year or greater after treatment completion among patients with HRGP who participated in rehabiltation.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the specific effects of stretching in recovery of GPI are not well known, allied to the lack of consensus in existing research and reduced statistical power of some individual studies [24,25], a systematic review may provide a summary of evidence and promote better informed clinical practice [26,27]. Recent, high-quality reviews on recovery from GPI are available [1,8,[10][11][12]14], but these were broad-scope works, considering a plethora of interventions, thus reinforcing our criticisms concerning the lack of assessment of unimodal interventions and consequently a poor knowledge of the effectiveness of each specific component of an intervention.…”
Section: Introductionmentioning
confidence: 99%